Respuesta :

Assuming that you're supposed to be solving for x, subtract 6x from both sides and then factor.

6x = 2x² - 8

0 = 2x² - 6x - 8

There are a couple different ways to factor, but I tend to like factoring by grouping wherever possible, which results in:

0 = 2x² + 2x - 8x - 8
0 = 2x(x+1) - 8(x+1)
0 = (2x - 8) (x + 1)

Now set each term equal to 0 and solve for x (If you just had to factor, you can ignore the rest of this).
0 = 2x - 8
8 = 2x
4 = x

and 

0 = x + 1
-1 = x

So overall, x = -1 and x = 4.